TRPM7 Induces Mechanistic Target of Rap1b Through the Downregulation of miR-28-5p in Glioma Proliferation and Invasion - Wan, Jingwei; Guo, Alyssa Aihui; Chowdhury, Indrajit; Guo, Shanchun; Hibbert, Jacqueline; Wang, Guangdi; Liu, Mingli (Frontiers in Oncology, 2019)
Objectives: Our previous findings demonstrate that channel-kinase transient receptor potential ion channel subfamily M, member 7 (TRPM7) is critical in regulating human glioma cell migration and invasion. Since microRNAs (miRNAs) participate in complex regulatory networks that may affect almost every cellular and molecular process during glioma formation and progression, we explored the role of miRNAs in human glioma progression by comparing miRNA expression profiles due to differentially expressed TRPM7. Methods: First, we performed miRNA microarray analysis to determine TRPM7’s miRNA targets upon TRPM7 silencing in A172 cells and validated the miRNA microarray data using A172, U87MG, U373MG, and SNB19 cell lines by stem-loop RT-qPCRs. We next determined whether or not TRPM7 regulates glioma cell proliferation and migration/invasion through different functional domains by overexpressing wild-type human TRPM7 (wtTRPM7), two mutants with TRPM7’s α-kinase domain deleted (Δkinase-DK), or a point mutation in the ATP binding site of the α-kinase domain (K1648R-KR). In addition, we determined the roles of miR-28-5p in glioma cell proliferation and invasion by overexpressing or under expressing miR-28-5p in vitro. Lastly, we determined whether or not Rap1b (a Ras-related small GTP-binding protein) is a target of miR28-5p in glioma tumorigenesis. Results: The miRNA microarray data revealed a list of 16 downregulated and 10 upregulated miRNAs whose transcripts are significantly changed by TRPM7 knock-down. Cell invasion was significantly reduced in two TRPM7 mutants with inactive kinase domain, Δkinase, and K1648R transfected glioma cells. miR-28-5p overexpression suppressed glioma cells’ proliferation and invasion, and miR-28-5p underexpression led to a significant increase in glioma cell proliferation and migration/invasion compared to that of the controls. miR-28-5p suppressed glioma cell proliferation and migration by targeting Rap1b. Co-transfection of siRap1b with miR28-5p inhibitor reduced the glioma cell proliferation and invasion, caused by the latter. Conclusions: These results indicate that TRPM7’s channel activity is required for glioma cell growth while the kinase domain is required for cell migration/invasion. TRPM7 regulates miR28-5p expression, which suppresses cell proliferation and invasion in glioma cells by targeting Rap1b signaling.